2018
DOI: 10.1002/cncr.31638
|View full text |Cite
|
Sign up to set email alerts
|

Trends in breast cancer mortality by stage at diagnosis among young women in the United States

Abstract: There were substantial improvements in the effectiveness of breast cancer treatment on overall and cancer-specific survival from 1975 to 2015. However, improvements appeared to have reached a plateau after 2005, except among young women with metastatic breast cancer, in whom survival continued to improve throughout the period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
107
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(112 citation statements)
references
References 46 publications
2
107
1
2
Order By: Relevance
“…Pathologic complete response to neoadjuvant systemic therapy in high-risk cancers such as triple negative and Her-2 driven cancers appear to be independent of stage I-III, and thus it is likely that the biological behavior of these tumors is dictated by chemosensitivity more than by their stage. Thus, Guo et al [21] in an excellent SEER-based study of breast cancer in young women concluded that screening has contributed little to the improvements in OS in this population. They concluded that even in the screened population of women > 40 "nearly all of the mortality reduction was caused by treatment advances and NOT screening".…”
Section: Discussionmentioning
confidence: 99%
“…Pathologic complete response to neoadjuvant systemic therapy in high-risk cancers such as triple negative and Her-2 driven cancers appear to be independent of stage I-III, and thus it is likely that the biological behavior of these tumors is dictated by chemosensitivity more than by their stage. Thus, Guo et al [21] in an excellent SEER-based study of breast cancer in young women concluded that screening has contributed little to the improvements in OS in this population. They concluded that even in the screened population of women > 40 "nearly all of the mortality reduction was caused by treatment advances and NOT screening".…”
Section: Discussionmentioning
confidence: 99%
“…Jacqueline et al 38 reported that the 5-year breast cancer net survival in females diagnosed between 2001 and 2009 was 88.2% independent of race and age, and the survival rates improved from the 2001 and 2003 to 2004 and 2009. Another study suggested that the 5-year breast cancer-speci c survival increased from 74.0% during 1975-1979 to 88.5% during 2010-2015 in women diagnosed between ages 20 and 39 years from the SEER database 20 . The data obtained in our research were slightly higher than previous studies, which might be due to the recent study year accompanied by the improved treatment methods.…”
Section: Discussionmentioning
confidence: 99%
“…Despite higher rates of LRR in young patients, several studies had shown a declining trend in the LRR rate over the past two decades [14][15][16] . In addition, there has been a signi cant decline in the occurrence of distant metastases (DM) 17,18 and increase in the overall survival over the last years in young breast cancer (YBC) patients owing to the evolution of improved adjuvant systemic treatment and raising consciousness of physical examination 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is among the most common malignancies and a leading cause of death in women [1]. However, advances in surgical techniques and systemic therapies have improved the survival of breast cancer patients in recent decades [2]. Breast cancer is a heterogeneous disease with a variety of pathologic and molecular features.…”
Section: Introductionmentioning
confidence: 99%